Evaluating mergers for coordinated effects and the role of 'parallel accommodating conduct' - Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2012)
The 2010 Horizontal Merger Guidelines propose a form of coordinated effects, referred to as "parallel accommodating conduct", that is claimed not to involve the usual evaluation of the ability of firms to detect compliance and punish non-compliance with respect to supracompetitive prices. That claim is argued here to be false. Where the concept of parallel accommodating conduct is valid and constructive is in identifying coordinated effects that do not involve firms having an agreement. These issues are explored here in the context of a more general examination of how firms coordinate on and implement supracompetitive outcomes.
Keywords: 330